Illusive Effects on the Diffusion of an Innovation: A Comment - Swanson, E. Burton; Fuller, Mary K.; Nidumolu, Sarma; Ramiller, Neil; Ward, Sidne G. (Management Science, 1991)
In their recent analysis of the effect of information sources and communication channels on the diffusion of innovation in data base development, Nilakanta and Scamell (1990) find a distinctive pattern of diffusion for both requirements analysis and logical data base design tools.